3-D reconstruction of an abandoned montane reservoir using UAV photogrammetry, aerial LiDAR and field survey. (September 2018) - Langhammer, Jakub; Janský, Bohumír; Kocum, Jan; Minařík, Robert
Abstract: The small reservoirs in the European montane landscape, which were built in past centuries for various purposes, represent specific cultural and technical heritage but also feature retention potential for mitigating the emerging impacts of climate change, namely, the course of flooding or droughts. However, the frequent lack of technical data on these historical structures, including their storage volume and flooded areas, prevents their consideration in water management planning. In this study, we used unmanned aerial vehicles (UAVs) to produce a detailed 3-D reconstruction of an abandoned montane reservoir that was built for timber flowing in the beginning of 19th century and that has not recently been used for any purpose. The UAV imaging and photogrammetric processing provided an ultra-high-resolution 3-D model of the reservoir basin (5 cm per pixel). Bathymetric analyses were performed based on this basin model to calculate the reservoir volume and flooded area for different water levels. The reliability of the UAV-based model was tested by comparing the results with those of elevation models derived from geodetic field survey using a total station and from conventional data sources based on available aerial LiDAR data. The data were compared to the historical estimates of the reservoir parameters found in the literature. Bathymetric reconstruction of the reservoir properties based on high-resolution UAV data revealed significant retention potential of the structure and historical underestimation of its capacity. The highly detailed UAV-based model helped to eliminate inaccuracies, resulting from the use of the generalized conventional elevation data, that affect the volumetric estimates in the flat topography of the reservoir basin. The study demonstrated the potential applicability of UAV technology for rapid and reliable reconstruction of landscape structures, which is significant for water management. Graphical abstract: Image 1 Highlights: UAV imaging, aerial LIDAR data and field survey were used for 3D reconstruction. High-resolution UAV data eliminated inaccuracies of 3D model in flat topography. UAV data revealed significant underestimation of the reservoir retention capacity. UAV technology enables rapid and reliable reconstruction of landscape structures. Small montane reservoirs can serve for mitigation of hydrometeorological extremes.